Evaluation of the Cognitive Level of the Students of Administration and Economics Collage / Mustansiriyah University on the Risks of Tattoos by using the Discriminant Analysis (Journal of the College of Basic Education, 2020)
The trend of tattooing in different areas of the body has recently spread in a noticeable manner in Arab societies in general, and among young Iraqis in particular, and it becomes an obsession that is increasingly popular for both sexes as a sign of freedom and keeping pace with fashion.There are many reasons for Iraqi youth to tattoo their bodies. These reasons were presented to a sample of the students of the College of Administration and Economics /the University of Mustansiriyah. A questionnaire was distributed to 400 students from the departments of the College of Administration and Economics of all phases of study through a questionnaire to classify and discrimination the main reasons lead to tattoo working, by using the discriminant analysis.The following results have been reached and showed that the variables (, the existence of mental disorders and behavioral deviations) in the first discriminant function, and (to draw attention to the location of the tattoo and highlight the strength and rigidity) in the second discriminant function, and the two variables ( to express an indication in the psychological aspect of the person who makes a tattoo), and (a try to having a more beautiful body or a more pompous image of the arm and body drawn to refer to a person who has been killed or bombed), and In the third discriminant function they had a high effect, they contributed positively to the causes of the phenomenon of tattoos, while the variables in the first and second discriminant functions, and in the third discriminant function have significant negative contribution to discrimination, as well as that the level of knowledge of the students of the first and second study phases about the tattoo health risk has been evaluated, which was weak for them, while it was average for the students of the third phase, and good for those of the fourth phase.